2013
DOI: 10.5194/bg-10-6403-2013
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variations in the Kuroshio nutrient transport from the East China Sea to south of Japan

Abstract: Abstract. Based on absolute geostrophic velocity, which was calculated using repeated hydrographic data of 39 cruises from 2000 to 2009 and nitrate concentrations measured in the same areas from 1964 to 2009, we obtained the temporally averaged nitrate flux (the product of velocity and nitrate concentration) and nitrate transport (integration of flux over one section) of four sections across the Kuroshio from the East China Sea (sections PN and TK) to an area south of Japan (sections ASUKA and 137E). In additi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 19 publications
2
53
1
Order By: Relevance
“…9b). In the Kuroshio area, the vertical mixing is also developed in the upstream and the nutrient-rich surface water supplies to our investigated area by the horizontal advective transport from the upstream area (Guo et al 2013). Thus, it was suggested that the surface nutrient concentration is not always reflected in the nutrient conditions of the subsurface/intermediated water.…”
Section: Other Possible Factorsmentioning
confidence: 87%
See 2 more Smart Citations
“…9b). In the Kuroshio area, the vertical mixing is also developed in the upstream and the nutrient-rich surface water supplies to our investigated area by the horizontal advective transport from the upstream area (Guo et al 2013). Thus, it was suggested that the surface nutrient concentration is not always reflected in the nutrient conditions of the subsurface/intermediated water.…”
Section: Other Possible Factorsmentioning
confidence: 87%
“…Thus, the horizontal advective transport was suggested to be the important factor of the nutrient concentrations, the same as for the Gulf Stream (Atkinson 1985;Lee et al 1991;Atkinson et al 1996). The horizontal advective transport from the Kuroshio area to the slope area could not be quantitatively evaluated because the nutrient concentrations were only obtained along the one latitudinal transect, and the current data were not analyzed in the present study, but Guo et al (2013) reported that the nutrient generally supplies from the slope area to the Kuroshio area along the 137°E transect. In addition, the T-S diagram in winter 2005 denotes that the Kuroshio water flows into the slope area (Fig.…”
Section: Other Possible Factorsmentioning
confidence: 89%
See 1 more Smart Citation
“…The mean nitrate transport of the Kuroshio along 137 • E, more downstream from the Tokara Strait, is significantly enhanced reaching an estimated value of ∼ 1000 kmol s −1 , which is comparable to the Gulf Stream transport (Pelegrí and Csanady, 1991;Pelegrí et al, 1996Pelegrí et al, , 2006Williams et al, 2011). Guo et al (2013) concludes that the Kuroshio recirculation has a significant contribution to the downstream increase of nitrate transport as occurred along the Gulf Stream (Williams et al, 2011). This is the first attempt to analyze nutrient and water mass transports in this region.…”
Section: Physical Forcing and Nutrient Transportmentioning
confidence: 77%
“…Based on the absolute geostrophic velocity, which was calculated from the repeated hydrographic data, and nitrate concentration measurements across five sections along the Kuroshio downstream during at least the last decade, Guo et al (2013) computed the nitrate transport by the Kuroshio Current from the ECS to south of Japan. Their estimated net nitrate transport crossing the PN line within the Okinawa Trough (Fig.…”
Section: Physical Forcing and Nutrient Transportmentioning
confidence: 99%